A Time- and Cost-Effective eDNA Protocol to Survey Freshwater Mussels (Bivalvia: Unionida) in Tropical Rivers - Alexandra, Zieritz; Tabitha, Richmond; Florian, Melzer; Khairul Adha, A. Rahim; Wilson, John-James; Hazeeqah Filzah, Kassim; Hanna, Hartikainen (John Wiley & Sons Ltd., 2025)
Tropical freshwater mussels (Bivalvia: Unionida) are one of the most endangered groups of animals globally, but conservation is hindered by a lack of species distribution data. Traditional hand-sampling is time- and cost-intensive and not always possible, for example, because of the presence of crocodiles. Surveying freshwater mussel populations by environmental DNA (eDNA) could potentially rapidly increase data availability, but no published study and protocols targeted towards tropical freshwater mussels are available to date. We aimed to develop a reliable and cost-efficient eDNA protocol for surveying tropical freshwater mussels. We first developed and validated a qPCR primer-probe assay within the cytochrome c oxidase subunit 1 (COI) gene for Rectidens sumatrensis. We applied this assay in a controlled laboratory setting on eDNA collected from lake and river water, respectively, at two different R. sumatrensis densities in order to test a set of 18 different protocols for capturing, preserving, and extracting freshwater mussel eDNA. All protocols use equipment that is readily available and reusable. Our results revealed that samples stored in Longmire's buffer (at 4°C) yielded more mussel DNA than when stored in absolute ethanol (at −20°C), with <1% of ethanol- and 78% of buffer-preserved samples fulfilling the criteria for positive R. sumatrensis eDNA detection (i.e., amplifying above the limit of detection in at least four out of five qPCR replicates). Across buffer-preserved samples, eDNA detection and amplification success rates were higher and quantification cycle values were lower for eDNA captured without pre-filtration and with filter membrane pore sizes >0.45μm, and eDNA extracted with the Qiagen DNeasy Blood & Tissue Kit rather than the PowerSoil ProKit (albeit latter exhibiting fewer instances of amplification in negative controls). The assay detailed here was capable of detecting down to R. sumatrensis eDNA concentrations of 6.38×10−7ng/μL and reflected the difference in stocking density.